2019
DOI: 10.1177/0972150918818604
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring Celebrity Equity: Unearthing the Consumer Knowledge Structure Associations

Abstract: The qualitative research aims to develop an understanding of how consumers view the celebrity as a brand and also to measure and compare the celebrity equities. This research applies associative network theory to identify the celebrity association networks residing in the minds of the consumers using Brand Concept Maps (BCMs) methodology. It also measures the celebrity equity by measuring the relative strength, favourability and uniqueness of the associations. Three celebrities from different professions are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Research has found that celebrity endorsers are more effective than various other types of endorsement techniques in creating brand awareness [27,30]. Despite the importance of this relationship, only a little evidence has been found on examining the effect of celebrity endorsement on brand sustainability awareness [31,32]. Therefore, the next hypothesis is: Hypothesis 3b.…”
Section: Attitude Towards Celebrity Endorsement and Brand Awarenessmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has found that celebrity endorsers are more effective than various other types of endorsement techniques in creating brand awareness [27,30]. Despite the importance of this relationship, only a little evidence has been found on examining the effect of celebrity endorsement on brand sustainability awareness [31,32]. Therefore, the next hypothesis is: Hypothesis 3b.…”
Section: Attitude Towards Celebrity Endorsement and Brand Awarenessmentioning
confidence: 99%
“…In this study celebrity and brand represent nodes, which are interlinked and associated to each other, such that when consumers think of a celebrity, they may actually think of the endorsed brand, and vice versa [24]. This linking could provide a desirable association conducive to the creation of brand awareness and brand value [32].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations